Multicenter, randomized controlled trial of traditional Japanese medicine, kakkonto with shosaikotokakikyosekko, for mild and moderate coronavirus disease patients - Takayama, Shin; Namiki, Takao; Arita, Ryutaro; Ono, Rie; Kikuchi, Akiko; Ohsawa, Minoru; Saito, Natsumi; Suzuki, Satoko; Nakae, Hajime; Kobayashi, Seiichi; Yoshino, Tetsuhiro; Ishigami, Tomoaki; et al. (Frontiers in Pharmacology, 2022)
The traditional Japanese (Kampo) medicine, kakkonto with shosaikotokakikyosekko, has antiviral and anti-inflammatory effects. In this randomized trial, patients with mild and moderate coronavirus disease (COVID-19) were randomly allocated to the control group receiving conventional treatment for symptom relief such as antipyretics and antitussives or the Kampo group receiving mixed extract granules of kakkonto (2.5 g) and shosaikotokakikyosekko (2.5 g) three times a day for 14 days in addition to conventional treatment. The main outcome was the number of days until total symptom relief. The secondary outcome was the number of days until each symptom’s relief and whether the disease progressed to respiratory failure. We enrolled a total of 161 patients (Kampo group, n=81; control group, n=80). The results from Kaplan–Meier estimates of symptom relief showed that there are no significant differences between the groups. However, covariate-adjusted cumulative incidence of fever relief considering competitive risk showed that the recovery was significantly faster in the Kampo group than in the control group (HR 1.76, 95% CI 1.03–3.01). Additionally, the risk of disease progression to moderate COVID-19 requiring oxygen inhalation was lower in the Kampo group than in the control group (Risk Difference -0.13, 95% CI -0.27–0.01). No significant drug-related side effects were observed. Kakkonto with shosaikotokakikyosekko is effective for fever relief with suppression of disease progression in COVID-19 patients.